Eulophia dabia - A Lesser Known Critically Endangered Terrestrial Orchid - Joshi, Bhavana; Panwar, G. S.; Singh, S. K. (Indian Forester, 2022)
Eulophia dabia (D.Don) Hochr is an endemic and critically endangered, species of the family Orchidaceae. It prefers to grow on sandy soil near water embankments. The tubers of this species are highly medicinal and used by the local healer for the treatment of various ailments. The present paper provides insight of its medicinal utility and their mode of propagation.